Multiliteracy Careful Reading Model Based on 21st Century Skills in Primary Schools - Tursiva, Erva; Rahman, Rahman; Ahwi, Rahmania Savitri (International Conference on Elementary Education, 2021)
Reading comprehension skills are one of the language skills that are often used in learning and everyday life, the reading comprehension skills of students in a classroom must be very diverse and can be categorized into three groups, namely students who have high, medium, and low reading comprehension skills. For students to have an optimal reading comprehension skill it is necessary to apply innovative learning, one of the alternatives is the use of a learning model. 21st-century skills are skills that students in the 21st century must have, as for these skills, namely communication skills, collaboration, critical thinking, and creative and innovative thinking. Multiliteracy careful reading model is a model that can be used to optimally improve reading comprehension skills. The purpose of this study is to describe the application of the careful reading model in reading comprehension learning, as an effort to encourage the development of 21st-century skills in elementary schools. This research uses a descriptive qualitative method. Data collection was carried out using a literature review. The results of this study can be concluded that the multiliteracy careful reading model in reading comprehension learning have learning stages that can accommodate 21st-century skills development.